Islamic Education Marketing Discourse From Maslahah Perspective - Sholikah Sholikah; Fatah Syukur; Mahfud Junaedi (FITK UIN Walisongo, 2020)
The marketing paradigm has undergone a change from the rational level to the emotional level, and finally, the shift in the spiritual level. Such discourse results in different marketing strategies, especially the marketing applied by both profit and non-profit organizations. Educational institutions, including non-profit organizations, must have a marketing strategy following the spiritual level shift. One spiritual aspect in the marketing of Islamic education is the level of maslahah (utility) applied to all marketing activities. The purpose of this study is to examine educational marketing from a maslahah perspective. This writing is library research with a qualitative descriptive approach—data sources in the form of references related to the study topic. Data analysis was carried out qualitatively, including data reduction, data presentation, and concluding. The results showed that the maslahah of Islamic education customers was the main objective of all Islamic education marketing activities.